Optimizing Communication Architectures in Heritage Buildings: A Decision Model for Transactional Kiosk Systems under Network Constraints - Iliev, Oleg (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This paper proposes a heritage-aware decision model for selecting communication architectures for transactional kiosk systems under infrastructure constraints. Using an AHP–TOPSIS framework and empirical evaluation, it compares protocols across LAN and hybrid KNX–IP environments, showing that hybrid solutions can ensure reliability with acceptable latency.